Determinan Kejadian ISPA pada Balita di Puskesmas Karang Dapo Kabupaten Musi Rawas Utara - Dwi Putri Sulistiya Ningsih; Ida Rahmawati; Mika Oktarina; Violita Siska Mutiara Siska Mutiara; Nurmalasari (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
Acute Respiratory Infection (ARI) is an acute infection process lasting for 14 days, caused by microorganisms and attacks one part, and or more of the respiratory tract, from the nose (upper tract) to the alveoli (lower tract), including adnexal tissue , such as the sinuses, middle ear cavity and pleura. Acute Respiratory Infection (ARI) always rank as first couse of death in infants and toddlers in Indonesia. There are many factors that cause infants and toddlers to suffer from ARI. This study aims to know the determinant the incidence of ARI in toddlers at the Karang Dapo Health Center, Musi Rawas Utara Regency.Methods, this study used a cross sectional design. The population is all patients toddlers in the Karang Dapo Health Center, Musi Rawas Utara Regency during 2017 as many as 529 toddlers. Samples were taken using simple random sampling technique as many as 84 people. Data were analyzed by univariate and bivariate with Chi-Square test (X2) and Contingency Coefficient (C). The Results, there is a significant relationship between the presence of smokers at home with the incidence of ARI in toddlers (p= 0.027) with a moderate relationship category (C = 0.261), there is a significant relationship between the healthy home factor and the incidence of ARI in toddlers (p= 0.000) with a tight relationship category (C=0.622), there was a significant relationship between the factory distance factor from home (p=0.000) and the incidence of ARI in toddlers with a moderate relationship category (C = 0.414). This research can be used as input in determining the health program for the Health Office and Health Center. Can be used as a source of teaching materials in the health sector both at STIKES Tri Mandiri Sakti and for references to other researchers.